(untitled) (Fiep Bulletin - online, 2011)
The work presented is the result of a project called "Childhood Father d’mare" developed in the class I and II of the Garden of Early Childhood Education Unit Pratinha-Belém-Pará, which aims to enhance the culture of Pará, preserving our traditions, expressions cultural movements and revelers all contributing to the development and upbringing of children, in an attractive and entertaining. Culture has an important role in children’s lives as it is seen as a social, historical and cultural. However, the child is not only the fruit of their cultural context, she is an active being, capable and producer of culture, to interact with toys sung, which requires movement, coordination and balance she changes the play and is changed by it. The methodology was organized through language-Body Gesture driving the emerging languages and the cultural, musical, intrapersonal and interpersonal. Learning situations strengthened several languages which promoted children’s socialization and interaction of children, as well as discoveries and creations produced on culture and movements recreated acquired by the child, to guarantee healthy growth and to live his childhood. Another important aspect was to exchange experiences and conversations of children with their parents or guardians seeking to expand the universe of games, in which this acquisition of knowledge has been reinvented for the little ones, as these are meaningful to children through challengesin a perspective of childhood guaranteed.